Assessing the legacy of red mud pollution in a shallow freshwater lake: long-term chemical recovery in the water column. Issue 4 (2nd October 2019) - Olszewska, Justyna P.; Heal, Kate V.; Edwards, Ronald; McDonald, Claire; Foster, Tim; Winfield, Ian J.; Spears, Bryan M.
ABSTRACT: Little is known about chemical and ecological recovery following red mud leachate pollution in fresh waters. This deficiency is confounded by a lack of knowledge on the chemical composition of red mud leachate and the changes in composition that occur as a result of interactions with sediments and freshwater organisms during transport through aquatic ecosystems. We used over 30 years of data from a shallow lake (Kinghorn Loch, Fife, Scotland) with a well-documented history of several decades of red mud leachate pollution to characterise the chemical loads (during a pollution period from 1981 to 1983), resultant impacts on surface water chemistry (comparison between 1983 and 2009), and recovery trajectories following leachate diversion (1983–2010) of constituents that pose a risk to the environment. Between 1981 and 1983, the input of leachate resulted in loads of total aluminium (Al), total arsenic (As), total vanadium (V), and phosphate (PO4 -P) to the lake of 107, 2.3, 3.3, and 2.3 g m −2 (lake surface area) yr −1, respectively. During the same period, the lake acted as a sink of Al, As, V, and PO4 -P, retaining 63.6, 0.6, 0.8, and 1.6 g m −2 yr −1, respectively. We used generalised additive modelling to assess the response trajectories and recovery end points of these constituents. Our results demonstrate the complexity of sediment–pollutant interactions during pollutant transport through the aquatic environment and provide insight into likely recovery trajectories in other aquatic ecosystems following red mud contamination. The PO4 -P, total As, and total V surface water concentration recovery times, defined statistically as the point on the time series beyond which no further significant decrease in concentrations was observed, ranged from 18 to 26 years. Total Al concentrations continued to decrease significantly following the end of the monitoring period in 2010. In Kinghorn Loch, the legacy of red mud pollution continues to represent an environmental risk, demonstrating the importance of long-term monitoring and management strategies following similar pollution events.